GREENFUSION: SYNTHESIS OF NEXT-GENERATION GREEN DIESEL FUEL THROUGH HYDRODEOXYGENATION OF NYAMPLUNG AND UCO - Maulana, Muhammad Ilham Rizky; Sinulingga, Fahri (Jurnal Geosaintek, 2026)
The urgency of the energy transition in Indonesia is becoming increasingly pressing due to the country's high dependence on fossil fuels and the presence of 5 million diesel vehicles. This research introduces "GreenFusion," a method for synthesizing green diesel to overcome the limitations of conventional biodiesel. The objective is to investigate the hydrodeoxygenation of a dual non-food feedstock mixture, specifically Calophyllum inophyllum (Nyamplung) oil and used cooking oil (UCO). The approach involves synthesizing a nickel-silver catalyst on natural zeolite (NiAg/ZH) and conducting the hydrodeoxygenation process in a batch reactor at temperatures between 325°C and 375°C. The results confirm the successful synthesis of high-quality green diesel with an estimated yield of 91,2% and a cetane number of 75. Environmental impact projections at the pilot scale indicate significant potential for reducing UCO waste and lowering CO2 emissions by over 1,200 tons per year. Therefore, GreenFusion presents a technically viable and environmentally superior pathway for producing drop-in fuel, supporting Indonesia's goal of achieving the 2060 Net Zero Emissions (NZE) target.